1989
DOI: 10.1520/jfs12623j
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Postmortem Interval Using Kinetic Analysis of the Third Component of Complement (C3) Cleavage

Abstract: To estimate postmortem interval (PMI), spontaneous cleavage of the third component of complement (C3) was studied in aged blood and cadaveric blood by crossed immunoelectrophoresis. Using the kinetics of C3 cleavage in vitro described as dC/dt = −kC, where C is the concentration of native C3 at time t and k is a first-order rate constant, Arrhenius' equation, and another equation which assumes a linear drop of body temperature after death, the percentages of C3 cleavage were calculated. There was a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Previous studies also showed that proteins in tissues and serum were degraded due to catabolic metabolism. 1,9,10,[13][14][15]37,38 Many proteolytic enzymes can be released from the lysosome during cell autolysis. The reduction of the absorption area of amide I confirms that ATR spectra also show the degradation of proteins after death.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies also showed that proteins in tissues and serum were degraded due to catabolic metabolism. 1,9,10,[13][14][15]37,38 Many proteolytic enzymes can be released from the lysosome during cell autolysis. The reduction of the absorption area of amide I confirms that ATR spectra also show the degradation of proteins after death.…”
Section: Resultsmentioning
confidence: 99%
“…A method has been described for the rapid HPLC analysis of a number of anticonvulsant drugs in vitreous humor by injection directly onto a preconcentration column without the need for prior extraction (305). A comparison was given of chemical methods for determining postmortem interval (306) and the estimation of postmortem interval by using kinetic analysis of the third component of complement (C3) cleavage (307).…”
mentioning
confidence: 99%